Chasing it - Heller, Buck; Velichko, Stephen; Peers Influence Peers Partnership; Soundview Media Partners (Putnam Valley, NY : Peers Influence Peers Partnership, Inc., 2014)
The explosion of heroin and other opiate abuse has affected more than those in Hollywood. One hundred Americans die every day from overdose deaths. The documentary tells the story of those affected and why heroin use has such a devastating reach.
"A documentary film about recovery from addiction."
Interviews with: Doug Greenwich, Marc Fishman, M.D., Aimie, Andre, Jamie, Justin, Mason, Michael, Shane.
Editors, Frank Reale, Stephen Velichko ; music, Michael Ferraiuolo.
In English.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed May 5, 2017).
Keywords: Heroin abuse -- United States; Addicts -- New York (State) -- Interviews; Nonfiction films; Documentary films; Internet videos; Streaming video